Sensory quality of selected natural yoghurts available on the Polish market - Agata Kiciak; Marcin Orzycki; Wiktoria Staśkiewicz; Agnieszka Bielaszka; Marek Kardas (Kazimierz Wielki University, 2022)
Introduction: The fermented milk drinks include: yogurt, kefir, fermented milk, acidophilic milk, koumiss and new generation dairy products. The high nutrient content of yogurt is related to the composition of the milk it is made of. Aim: The aim of the study was to assess the sensory quality of selected natural yoghurts available on the Polish market.Material and methods: The research material consisted of 8 natural yoghurts available on the Polish market. Natural yoghurts were purchased in supermarkets in the Silesian Voivodeship. The intensity of the examined features (color, taste, smell, consistency, general appearance) was assessed using a proprietary card for evaluation on a five-point scale (5 - very good quality, 1 - disqualifying quality). Results: The results of the sensory evaluation using the 5-point method: The highest mean was obtained by the yoghurt code: 125 - 4.34 (± 0.47) and the worst by the respondents was the yogurt with the code: 596 - 3.54 (± 0.77). The results of the sensory evaluation carried out by the scheduling method: the highest scores were obtained for natural yoghurts with the codes 133 and 189.Conclusions: The evaluation of the sensory quality of selected natural yoghurts carried out using the five-point method showed that the highest overall score was obtained by yogurt containing: milk, powdered milk, milk proteins, calcium, live cultures of yoghurt fermentation bacteria, Lactobacillus acidophilus LA-5® i Bifidobacterium BB-12®.The evaluation carried out by the ranking method showed that yoghurts with the following compositions were best evaluated by the respondents: milk, milk proteins, live yoghurt bacteria cultures and milk, live bacteria cultures, selected lactic acid strains of Bifidobacterium BB-12®, 0% fat.The lowest score of respondents in the sensory evaluation with the use of both methods was obtained by natural yoghurt with the following composition: milk, live bacteria cultures.